Prospective transnational migrant workers’ language practices during internal migration - Subida, Maharlika Rogelita; Ponce, Ariel Robert (Journal of Modern Languages, 2025)
This study examines the language practices of prospective Filipino migrant workers who temporarily relocate to Metro Manila to complete pre-departure activities to secure a job opportunity abroad. Using self-reported language logs, the study documents 450 communicative events across familial, professional, and social domains. Findings show that Tagalog is the most frequently used language, functioning as both a practical lingua franca and a culturally anchored medium in the metropolis. Local languages remain vital within familial and interpersonal interactions, reinforcing regional identity despite urban pressures. English meanwhile is used predominantly in formal and professional transactions, while Taglish (Tagalog-English) serves as a flexible hybrid language that bridges communicative demands across contexts. Overall, the study highlights how in-migrants negotiate linguistic adaptation and cultural continuity, offering insight into the complex dynamics of language shift during internal migration in the Philippines.